Bankruptcy risk, firm size, and firm profitability: a dynamic panel data approach. (9th January 2023) - Yousaf, Muhammad
The main purpose of this study is to examine the impacts of bankruptcy risk of small and medium enterprises (SMEs) and large firms on firm profitability. By employing the secondary data from the CRIBIS database of the Czech firms from the ten sectors, the bankruptcy risk is measured by Altman model and Springate model. This is the first study examining the impacts of the firm size on firm profitability by simultaneously employing the Altman and Springate models. We employed the two-step system generalised method of moments (GMM) to estimate the regression models. The findings revealed three important results: 1) there is a positive relationship between the bankruptcy models and firm profitability; 2) SMEs earn more profits than large firms; 3) the bankruptcy risk for SMEs is higher than the large firms.